1955
DOI: 10.1172/jci103132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Supine Position on Renal Function in the Near-Term Pregnant Woman12

Abstract: It has been demonstrated previously that urine flow in the recumbent near-term pregnant woman is appreciably less when she is lying on her back than when she is lying on her side and that without change of position the relative oliguria persists for several hours before it is overcome (1, 2).The present report extends the observations on the effect of position on urine flow to include studies of sodium and potassium excretion, effective renal plasma flow, and glomerular filtration rate in near-term normal preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1964
1964
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Previous studies had shown that assumption of a supine posture results in an immediate decrement in urinary sodium excretion (11,31). Our data extend this observation by demonstrating that supine recumbency is antinatriuretic despite considerable volume loading and even when the GFR remained above lateral recumbent control values.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Previous studies had shown that assumption of a supine posture results in an immediate decrement in urinary sodium excretion (11,31). Our data extend this observation by demonstrating that supine recumbency is antinatriuretic despite considerable volume loading and even when the GFR remained above lateral recumbent control values.…”
Section: Discussionsupporting
confidence: 85%
“…The decrease in filtered sodium has been mentioned as a causal factor (33), but in this study volume expansion before changing position resulted in a number of instances in which supine recumbency was antinatriuretic despite an increased filtered load. The increase in caval pressure induced by supine recumbency has also been implicated (31,(34)(35)(36), since in man congestion of the inferior vena cava induced by an inflatable balloon consistently reduced urinary sodium excretion (37). We have no data to support or deny this sug-'Lindheimer, M. D., and P. V. Weston.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, obstruction to the inferior vena cava at the level of entry of the renal veins automatically implies increased renal venous pressure. The effects of posture on renal function in late pregnancy have already been described (Pritchard, Barnes, and Bright, 1955), and we are currently pursuing these investigations. Finally, it is apparent that posture has profound effects on the circulation in late pregnancy, and this must be carefully considered in any haemodynamic or renal studies in pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…In pinnipeds and sloths the spinal veins are normally the only avenue for venous return from some parts of the body (Wislocki, 1928;Harrison and Tomlinson, 1956). The plexus also acts as a vascular bypass during transient increases in thoracoabdominal pressure induced by coughing and defecation (Batson, 1957), micturition (Herlihy, 1948), lifting and the Valsalva maneuver (Batson, 1957;Eckenhoff, 1970), abdominal tumors (Pritchard et al, 1955;Scott, 1963), position of the viscera (Herlihy, 1948), pregnancy (Hirabayashi et al, 1996), activity of the abdominal muscles (Youmans et al, 1963), normal respiration (Reitan, 1941;Herlihy, 1948;Brecher, 1956;Eckenhoff, 1970), and the manual application of external pressure (Batson, 1940(Batson, , 1957Herlihy, 1948;Epstein et al, 1970; but see Worthman, 1956b). Under these various conditions, caval venous pressures rise sharply (e.g., Brigden et al, 1950;Scott, 1963) and blood is forced out of the thoracoabdominal veins and shunted into the plexus.…”
Section: Functional Considerationsmentioning
confidence: 99%